2021
DOI: 10.1186/s12888-021-03644-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementing individual placement and support (IPS): the experiences of employment specialists in the early implementation phase of IPS in Northern Norway. The IPSNOR study

Abstract: Background For decades there has been a continuous increase in the number of people receiving welfare benefits for being outside the work force due to mental illness. There is sufficient evidence for the efficacy of Individual Placement and Support (IPS) for gaining and maintaining competitive employment. Yet, IPS is still not implemented as routine practice in public community mental health services. Knowledge about implementation challenges as experienced by the practitioners is limited. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
1
27
0
1
Order By: Relevance
“…It's interesting to note that all PES staff significantly decreased their positive attitudes towards specific questions regarding integration of employment support with health services and time unlimited support. These principles rely on close and timely collaboration between sectors, and although we see a large scale‐up of IPS in Norway, integration challenges are one of the biggest barriers (Fyhn et al, 2021; Moe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It's interesting to note that all PES staff significantly decreased their positive attitudes towards specific questions regarding integration of employment support with health services and time unlimited support. These principles rely on close and timely collaboration between sectors, and although we see a large scale‐up of IPS in Norway, integration challenges are one of the biggest barriers (Fyhn et al, 2021; Moe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Professionals who deliver these interventions are expected to adopt a trust‐based logic, while at the same time, they need to empower the individual through various bureaucratic, external organisations (such as receiving financial support from the social services, the Social Insurance Agency or the Public Employment Agency). System factors and the government‐controlled regulations of the diverse organisations are often incompatible with the logic of the recovery‐oriented interventions of HF and IPS and both interventions require policy accommodations on every level (Benjaminsen, 2014; Moe et al, 2021) Conflicts between values and different systems may pose challenges when the interventions are implemented (Moe et al, 2021), and informal, unspoken hierarchies as well as obvious differences in cultures and formal regulations can create problems. At the same time, national guidelines advocate implementation and person‐centred interventions and thus collaboration between agencies should be based on the users' best interests, but without clarifying how contrasting and often directly contradictory interventions should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Although IPS measures of efficacy are generally robust, even across different welfare systems (Brinchmann et al, 2020), it is suggested that the actual implementation of IPS in real world settings may be more influenced by contexts as country or culture (Moe et al, 2021) and may pose organisational challenges to decentralised and/or specialised welfare states (cf. Moe et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IPS is more effective than other programs, it is complicated to implement this model in both the Netherlands and other countries [11][12][13][14][15][16][17][18]. Inadequate funding and cooperation between mental health care and vocational rehabilitation services appear significant barriers to enhance further implementation in practice [4, 11-15, 17, 19-22].…”
Section: Introductionmentioning
confidence: 99%